Spatiotemporal beta diversity of plankton species and their interactions in permanent and temporal waterholes in a semiarid savannah. Issue 4 (2nd October 2021) - Hulot, Florence D.; Msiteli-Shumba, S.; Iung, Mathias; Noûs, Camille; Thébault, Elisa
ABSTRACT: Freshwater communities can vary greatly across space and time. Studying these variations (i.e., spatial and temporal beta diversity) provides fundamental information on the processes that maintain diversity and on the consequences of environmental changes on communities. Recently, drying events have been shown to strongly affect the spatial and temporal beta diversity of temperate freshwater ecosystems, but the effects of such events are mostly unknown for freshwater communities in semiarid climates frequently submitted to drying up. In addition, studies have so far focused on variations in species composition (i.e., species beta diversity), but variations in species trophic interactions (i.e., food web beta diversity) can give additional insights on how community functioning varies in space and time. We combined species and food web perspectives to explore the spatiotemporal beta diversity of plankton species and their trophic interactions in waterholes undergoing different water level regimes: either an alternation between dry and water-full states, or a permanent water-full state due to water pumping. Our results show that waterholes with artificial water pumping do not differ from natural waterholes in their contribution to spatiotemporal beta diversity. Instead, beta diversity is strongly driven by temporal variations of species composition and food web structure during the dry season, which is characterized by degraded planktonic communities with a low richness, diversity, and connectance. Species- and interaction-based approaches give complementary information on the spatiotemporal beta diversity by highlighting different planktonic communities with contrasted functioning.